The influence of service quality, product quality, and product price on consumer satisfaction at teras malioboro 1 yogyakarta - Wigati, Erna; Isnugroho, Endro; Widayati, Endang; Haryanto, David Ramadhan Putra; Kustini, Henny (Surya Hijau Manfaat, 2024)
This research aims to determine the effect of service quality, product quality, and product price on consumer satisfaction at Teras Malioboro 1 Yogyakarta. Teras Malioboro 1 Yogyakarta is located on Jalan Margo Mulyo, Ngupasan, Gondomanan, Yogyakarta City. This study uses primary data with a questionnaire method where the number of respondents is 100 respondents selected using purposive sampling technique with a quantitative approach carried out using multiple linear regression analysis with normality test, multicollinearity test, heteroscedasticity test, determination coefficient test (R²), t-Test, and f-Test. The results of the tests carried out indicate that service quality has a significant effect (α = 5%), product quality does not have a significant effect (α = 5%) and product price has a significant effect (α= 5%) on consumer satisfaction at Teras Malioboro 1 Yogyakarta with a significant (α = 5%). With the percentage obtained from the determination coefficient test is 80.2% and proven by the researcher's observation with the existence of good service quality, product quality, and product prices in a purchase, it will create satisfaction for its consumers and play an important role in forming consumer satisfaction.